2013
DOI: 10.2147/opth.s44407
|View full text |Cite
|
Sign up to set email alerts
|

Scleral buckling for retinal detachment in Ibadan, Sub-Saharan Africa: anatomical and visual outcome

Abstract: BackgroundScleral buckle surgery is not a commonly performed surgical procedure in Sub-Saharan Africa due to a paucity of trained vitreo retinal surgeons. The aim of the study was to review sclera buckle procedures with a view to evaluating the anatomical and visual outcomes.MethodsCase records of patients that had scleral buckle surgery at the Retina Unit of the University College Hospital, Ibadan, Nigeria, between 2007 and 2010 were reviewed. Information retrieved included patients’ demographics, duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…In group A (2002–2005), retinopexy was achieved through cryotherapy and in group B (2011–2014) retinopexy was done using postoperative 532 nm laser photocoagulation. The anatomic success rate in this study was comparable with other studies 1,3,4,8,10–13. Avitabile et al evaluated the efficacy of cryotherapy vs transpupillary laser retinopexy in a randomized prospective study of 703 patients with RRD undergoing SB 14.…”
Section: Discussionsupporting
confidence: 84%
“…In group A (2002–2005), retinopexy was achieved through cryotherapy and in group B (2011–2014) retinopexy was done using postoperative 532 nm laser photocoagulation. The anatomic success rate in this study was comparable with other studies 1,3,4,8,10–13. Avitabile et al evaluated the efficacy of cryotherapy vs transpupillary laser retinopexy in a randomized prospective study of 703 patients with RRD undergoing SB 14.…”
Section: Discussionsupporting
confidence: 84%
“…Another study done by Oluleye et al .,[ 12 ] also showed anatomical attachment success in 40 eyes (90.9%) at the 1 st day postoperatively and in 32 eyes (86.5%) at 6 weeks after scleral buckle surgery. In a study done on 43 eyes of patients who underwent scleral buckling and cryopexy, anatomic success was achieved in 95.3% of eyes.…”
Section: Discussionmentioning
confidence: 92%
“…The superiority of scleral buckle in terms of final visual acuity and the occurrence of postoperative cataract in uncomplicated phakic RRDs were showed. [ 8 9 10 11 12 ] The aim of this study is to highlight the anatomical and visual outcomes of scleral buckling surgery in relation to the pattern of presentation of rhegmatogenous RD in the presence of different situations and risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies from SSA have reported on the burden of RD and outcome of its treatment. [21][22][23] In one study RRD repair was the commonest indication (62%) out of a thousand vitrectomies performed in a single vitreoretinal unit in Nigeria. 23 RRD was associated with a higher degree of PVR, which is a poor prognostic feature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from SSA have reported various levels of success using scleral buckling technique for repair of RRD in the region. 21,22 However, vitrectomy will be required for the more complex forms of RD including the advanced PVR RRD and TRD. 23 AMD was a common retinal finding in studies from Nigeria.…”
Section: Discussionmentioning
confidence: 99%